High Mean Platelet Volume Associates with In-Hospital Mortality in Severe Pneumonia Patients - Jieru Chen; Yihao Li; Yingsi Zeng; Yu Tian; Yueqiang Wen; Zebin Wang (Hindawi Limited, 2020)
Background. Although mean platelet volume (MPV) appears to be associated with poor outcome of pneumonia, the relationship between MPV and in-hospital mortality is unclear in severe pneumonia (SP) patients. Methods. In this retrospective cohort study, 115 SP patients from June 1st, 2016, to September 29th, 2019, were included and divided into two groups. The primary outcome was in-hospital mortality. The receiver operating characteristic (ROC) curve was performed to assess the predictive ability for in-hospital mortality. Kaplan-Meier cumulative incidence curves were applied to observe the incidence of mortality. Multivariable Cox regression analyses were used to evaluate the hazard ratios (HRs). Besides, a formal test for interaction was investigated to analyze the relationship between MPV and sex. Results. During the course of hospitalization, 63 cases of mortality were recorded. ROC analysis suggested that MPV had a modest power for predicting in-hospital mortality (AUC=0.723, 95% CI: 0.628-0.818, P<0.001). Yet the cutoff value of MPV was 10.5 (sensitivity=73.02%; specificity=73.08%). Compared to the low-MPV group, the high-MPV group had significantly increased in-hospital mortality (log-rank test=13.501, P<0.001), while the adjusted Cox model indicated that the high-MPV group was associated with an elevated risk of in-hospital mortality (HR: 2.267, 95% CI: 1.166-4.406, P=0.016). Moreover, analyses of in-hospital mortality suggested a significant interaction between optimal MPV level and sex (P=0.011). In a multivariate Cox model which included females only, a high MPV level was associated with increased risk of in-hospital mortality (HR: 11.387, 95% CI: 1.767-73.380, P=0.011). Conclusion. High MPV level is an independent risk factor for in-hospital mortality in patients with SP.